A study on the correlation between financial ratios and earnings per share in South Korean banking - Li, Wei Jie (2009)
It is very important to evaluate bank performance for shareholders, investors, and regulators. Lots of criterion have been set. Abundant researches have been done on banks in Western Europe, North America, Australia, and Japan. However, only a few studies have been completed on banks in East Asia region, and very few were on individual East Asian country. Our research aims to explore whether performance determinants that have been proved influential in Western countries also apply to the individual East Asia context. These determinants include Earnings, Asset, Growth, Liquidity, Equity, and Strategic Response Quotient, that is, the components of EAGLES model which is propounded by Vong (1994) of Nanyang Technological University in recent years. The measurements of bank performance, expressed in Earnings Per Share (EPS) and Earnings Per Share Growth (EPSG), are evaluated in this study. Analysis is performed based on sample database comprising nine banks from South Korea over 1992-1995. The multiple regression method is used to determine bank performance by statistical relationship between the key determinants and EPS and EPSG.